The Academic, Affective and Linguistic Factors that influence the level of English Achieved by EFL Learners majoring in the B.A. in English Teaching Option and the B.A in Modern Languages Specialization in French and English at the Foreign Languages - Gavidia Pineda, Valeria Xiomara; Hernandez Rivera, Johana Jazmin; Sanchez de Sierra, Yeny Nathaly (2024)
The present research is focused on the study of the academic, affective, and linguistic factors that influence the level of English achieved by EFL learners at the FLD of the University of El Salvador. This work has been conducted as a bibliographical research. For instance, the data has been collected through investigating other studies carried out at the FLD. The findings of this research are shown by using graphs and tables taken from previous studies to have a clear understanding of the phenomenon. Therefore, the team expects the results obtained from the sources consulted will be helpful to find the impact of academic, affective, and linguistic factors in the level of English achieved by students from the FLD. Based Words: Grade point average (GPA), Academic background, socioeconomic status (SES), study habits, attitude, anxiety, shyness, motivation, vocabulary, grammar, pronunciation, vocabulary, and phonetics.